Social capital an international research program - Lin, Nan 1938-; Erickson, Bonnie H. (Oxford University Press, 2008)
For two decades, a significant number of scholars have subscribed to a common definition of social capital (resources embedded in social networks), employed a standard measurement (the position generator methodology), and conducted original research. Their sustained efforts have demonstrated the power of the concept of social capital in diverse arenas of research and varied cultural and societal settings. Their work has contributed to the substantiation, development, and expansion of social capital as a key scientific concept and theory. This book presents an introduction to some of the most recent work in the area. The volume editors have brought together scholars from North America, Europe, and East Asia to offer original and accessible reports of their own research studies. Covering both methodological and substantive issues, they demonstrate the continued importance of social capital as a guiding concept and theory in social sciences today.